KEBIJAKAN KEMENTERIAN AGAMA REPUBLIK INDONESIA TENTANG PENETAPAN SATU RAMADHAN DAN SATU SYAWAL DALAM UPAYA PENYATUAN UMAT ISLAM DI INDONESIA - Hidayat, Abdul Hakim Taufik; Izomiddin, Izomiddin (Muamalah, 2019)
The difference between the determination of the beginning of Ramadhan and Shawwal is always a warm and prominent discussion. This classic but actual problem becomes very complicated when the nation faces a certain Islamic month. The months that are very significant towards the concentration of Muslims, in the determination of the beginning of the month are Ramadan, Shawwal, and Dhu al-Hijjah, which often becomes the subject of discussion and determination in their determination and determination in Indonesia. This study aims to understand and explain the form of legal rules issued by the Government and the position and legal strength of the Decree of the Minister of Religion concerning the Establishment of One Ramadan and One Shawwal and to analyze how the legal decisions produced by the Decree of the Minister of Religion are viewed from the aspect of Human Rights (HAM) ) and the Obligations of Citizens for Efforts to Unite Muslims in Indonesia. Keyword: Franchise, Business, Islamic Law